2018
DOI: 10.1051/matecconf/201815005050
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Students’ Experience Towards the Development of Alumni Involvement and Alumni Loyalty

Abstract: The purpose of this study is to investigate the influence of students’ experience towards the development of alumni involvement and alumni loyalty in Malaysia. This study utilized the survey (questionnaire) method. Data are gathered from 347 respondents in one of the Public Higher Educational Institution (PHEI) in Malaysia. Results presented that students in this institution have low levels of alumni involvement (mean=1.23) and alumni loyalty (mean=1.76). Results also presented that in this institution, studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…From the literature review, these findings are consistent with the previous findings as reported by various researchers (e.g. Ropp, 2014;Saraih, et al, 2018;Hennig-Thurau, 2001). For example, Ropp (2014) reported that undergraduates who were provided with the institutional support they needed to accomplish their academic goals, were more likely to donate back to their alma mater.…”
Section: Hypotheses Testingsupporting
confidence: 92%
See 3 more Smart Citations
“…From the literature review, these findings are consistent with the previous findings as reported by various researchers (e.g. Ropp, 2014;Saraih, et al, 2018;Hennig-Thurau, 2001). For example, Ropp (2014) reported that undergraduates who were provided with the institutional support they needed to accomplish their academic goals, were more likely to donate back to their alma mater.…”
Section: Hypotheses Testingsupporting
confidence: 92%
“…For example, Ropp (2014) reported that undergraduates who were provided with the institutional support they needed to accomplish their academic goals, were more likely to donate back to their alma mater. Similar findings by Saraih et al (2018) showed that students who have a positive and satisfying experience while enrolled tend to develop lifelong relationships as alumni with their collegiate institutions. Also, a study of academic experience by Hennig-Thurau et al (2001) found that the quality of teaching experienced by students serves as a foundation of alumni loyalty.…”
Section: Hypotheses Testingsupporting
confidence: 63%
See 2 more Smart Citations